2015 IEEE International Conference on Robotics and Automation (ICRA) 2015
DOI: 10.1109/icra.2015.7140057
|View full text |Cite
|
Sign up to set email alerts
|

Developing and benchmarking show & tell robotic puppet for preschool education

Abstract: Robots have been shown to assist in education and development of social skills in children. However, there has been no study yet that benchmarks the effectiveness of robots with respect to traditional playtools found inside a classroom, such as pretend play items and blocks. This paper presents the design, development and testing of robotic puppets, which would be used to support teaching in kindergarten education. Different types of robotic puppet design were considered before settling on a glove-type puppet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Fifty-two five-year-old children were observed to assess the robot's performance, from which quantitative and qualitative data were collected. The study indicated that robotic toys could improve learning, creativity, imagination, and interaction (Causo et al, 2015).…”
Section: Related Workmentioning
confidence: 96%
“…Fifty-two five-year-old children were observed to assess the robot's performance, from which quantitative and qualitative data were collected. The study indicated that robotic toys could improve learning, creativity, imagination, and interaction (Causo et al, 2015).…”
Section: Related Workmentioning
confidence: 96%
“…We define social robots as physically embodied autonomous robotic technology, equipped with artificial intelligence and social skills, developed to become equal partners in social relations, capable of human‐like situational and role appropriate interaction (Istenic et al., 2021). At this stage, however, research and development in the field of social robotics still tend to focus more frequently on technology applications (Causo et al., 2015; Park, Han, et al., 2011; Verner et al., 2016), human–robot interaction (HRI) (Keren et al., 2012; Lücking et al., 2016) and affective outcomes (Belpaem et al., 2018), for example, motivation and engagement (Brown & Howard, 2014), than on the instructional robot's use in different curricular areas (Crompton et al., 2018; Rosanda & Istenic Starcic, 2019, 2020). There are few studies examining social robots performing teaching roles (Fernández‐Llamas et al., 2018).…”
Section: Introductionmentioning
confidence: 99%